La Casa . The House - Cortés, Tayo (Devenir Producciones, Andoliado Producciones, 2009)
Verzio FF The Méndez family has been living in a makeshift wooden cabin in the hills outside Bogotá for 40 years, yet they can be evicted any time. Every day they walk down to the city to collect scrap materials to sell, and leftovers from restaurants to feed their pigs. Victor has been married to Marta for ten years, but Elvira, his mother, has never come to like her. The clash between these two women forces Victor to take sides and comes in the way of their efforts to earn a living. The conflict further escalates when an armed neighbor claims their land. A distressing yet hopeful insight into a world of social tensions and existential helplessness on the outskirts of the Columbian capital, this film bears witness to the persistence of dreams for this family of scrap merchants.